Factors influencing veterinary surgeons’ decision-making about dairy cattle vaccination - Richens, I.F.; Hobson-West, Pru; Brennan, Marnie L.; Hood, Z.; Kaler, Jasmeet; Green, M.; Wright, N.; Wapenaar, Wendela (BMJ Publishing Group, 2016)
The use of vaccines in the cattle industry is widespread; however, there is limited published guidance for use by decision-makers such as farmers and vets. To best support vets in advising dairy farmers on the optimisation of vaccination strategies, it is important to understand how and why vets make decisions about recommending the vaccination of cattle. The objective of this study was to explore in-depth farm animal vets’ motivators and barriers to the implementation of vaccination strategies on British dairy farms. Semistructured interviews were conducted with 15 vets. Results indicated that vets have a positive attitude towards the use of vaccination and have few barriers to advising its implementation. Vets appear to group farmers into three ‘character types’. This characterisation influences the vet–farmer relationship and how the vet communicates with the farmer. Vets required evidence of disease or a risk of disease as a motivator to advise vaccination. However, this seemed to be sometimes overruled by a risk-averse attitude; resulting in vaccination being advised ‘just in case’. Crucially, the need for resources to support and build on the vet–farmer relationship is highlighted as an area requiring further exploration in order to optimise vaccination strategies on farm.